The Boy : A Novel - Hoag, Tami; Huber, Hillary ([Grand Haven, Michigan] : Brilliance Audio, 2018)
In the town of Bayou Breaux, Louisiana, a seven-year-old boy has been murdered and a thirteen-year-old girl is missing. With pressure mounting, Nick and Annie dig deep into the dual mysteries.
Keywords: Murder -- Fiction -- Investigation; Parental grief -- Fiction; Missing children -- Fiction; Louisiana -- Fiction; Audiobooks; Detective and mystery fiction